Pengaruh Model PJBL terhadap Hasil Belajar pada Pembelajaran Tematik Di Kelas IV SDN Kota Bengkulu - Tiara Apriliyani; Sri Dadi; Dalifa Dalifa (JURIDIKDAS, 2019)
This study aims to determine the effect of Project Based Learning (PjBL) model on student learning outcomes in thematic learning. This research is a quantitative research. The research method used is Quasy Experimental with design type The Matching Only Pretest Posstest Control Group Design. The population of this study is the students of class IV group 14 Kota Bengkulu. The sample in this research is class IV B SDN 42 Kota Bengkulu and class IV B SDN 45 Kota Bengkulu. The sampling technique used Cluster Random Sampling. The sample size of 52 students consists of grade IV B SDN 42 Kota Bengkulu totaling 25 students as experimental class and grade IV B SDN 45 Kota Bengkulu totaling 27 students as control class. The research instrument used in the form of test of cognitive learning result in the form of multiple choice questions (Multiple Choices) given through Pretest and Posttest, for learning result of attitude aspect and instrument skill that used is observation sheet. Taking the test twice, ie before and after the learning in the experimental class and control class. Based on the results of the percentage of learning outcomes obtained by the experimental class on the subjects of Civics, Indonesian, IPA is 55.2%, 47.9%, 50% while in the control class of learning outcomes obtained on subjects of Civics, Indonesian, 41.04%, 30.3%, 21.7%. This indicates that there is a significant effect of the students' learning outcomes on Thematic learning using Project Based Learning (PjBL) model.